What Ever Happened to My Peace of Mind? Hag Horror as Narrative of Trauma - Fisiak, Tomasz (Text Matters: A Journal of Literature, Theory and Culture, 2019)
In his pioneering study of Grande Dame Guignol (also referred to as hag horror or psycho-biddy), a female-centric 1960s subgenre of horror film, Peter Shelley explains that the grande dame, a stock character in this form of cinematic expression, “may pine for a lost youth and glory, or she may be trapped by idealized memories of childhood, with a trauma that haunts her past” (8). Indeed, a typical Grande Dame Guignol female protagonist/antagonist (as these two roles often merge) usually deals with various kinds of traumatic experiences: loss of a child, domestic violence, childhood abuse, family conflicts or sudden end of career in the fickle artistic industry, etc. Unable to cope with her problems, but also incapable of facing the inevitable process of aging and dying, she gradually yields to mental and physical illnesses that further strengthen the trauma and lead to her social exclusion, making her life even more unbearable. Unsurprisingly, scholars such as Charles Derry choose to name psycho-biddies horrors of personality, drawing attention to the insightful psychological portrayal of their characters. Thus, it would be relevant and illuminating to discuss films such as Die! Die! My Darling! (1965) and Whoever Slew Auntie Roo? (1971) as narratives of trauma. This will be the main concern of my article.